New charity economy and social work: Reclaiming the social dimension of public life in the context of changing welfare rationales - Griet Roets; Fabian Kessl; Walter Lorenz (Social Work and Society)
A complex historical transformation of the institutional framework of the welfare state is taking place changing the relationship between citizens, the state, civil society, and the market, which leads to an emerging so-called charity economy. The key question we address is how social work and social pedagogy can continue to fulfil their public and professional mandate while changing welfare rationales increasingly constrain its social justice and human rights aspirations. We will discuss and illustrate how this new charity economy has gradually emerged on the level of local welfare systems in Belgium, relying on dialectics that enable us to untangle changing welfare rationales. We conclude that social work and social pedagogy should stage a political struggle to radicalize democratic debate on complexities and frictions in welfare systems in the local, national, and global realms.